واقع القطاع الزراعي وأثاره على التنمية الزراعية للعراق للفترة(1990- 2008) (المجلة العراقية للعلوم الاقتصادية, 2018)
The agricultural development Takes has an important and distinct place not in the Iraqi economy only, but in most economies of the world because of its important role in the growth and development of the agricultural sector .In Iraq it was and is still there is an urgent need for the state's role in the development of the agricultural sector, due to the weak financial technological and administrative capabilities, of agricultural sector, when the state agricultural sector during the period of the economic embargo that has committed to Iraq through its agricultural policies so are good at it succeeded in providing food and food security, even lowerat levels for the Iraqi people, but when stopped the state from providing the required support after the occupation at the time that the agricultural sector has suffered from the destroy and undermine infrastructure and the problem of water, desertification and exposure of the Iraqi economy and the spread and prevalence of dumping in the Iraqi market, we find that the levels of agricultural production has fallen dramatically from what it was in a period of economic blockade and before the occupation.